Intimate revelations: conversations among ‘evil’ women in Rokeya’s Padmarag - Hasan, Md. Mahmudul (2016)
In Indian metaphysics, the legend of Khana and her husband Mihir illustrates how a praiseworthy trait for men can potentially become a blameworthy one for women. One day, as Mihir and his father were struggling to unravel an astrological question, Khana’s intervention helped them solve the problem right away. However, her superior intellect made Mihir apprehensive of the possible loss of his male superiority and power. Feeling threatened, Mihir reacted with antagonism and cut off her tongue in order to end her ability to express herself. Thus, instead of being appreciated, Khana’s superior knowledge encountered mistrust and hostility. Similar gendered double standard was prevalent in Rokeya Sakhawat Hossain’s (1880-1932) early twentieth-century Bengal where the pursuit of education and social work were considered commendable for men, but when she administered motivational work for her Sakhawat Memorial Girls’ school, she was accused of flaunting and peddling her youthfulness by way of establishing an educational institution. This is because, while what Rokeya did was considered a male preserve, the association of women and evil was embedded in her cultural context. Rokeya depicts this in her fiction Padmarag (1924) where she brings about an assemblage of women on the premises of Tarini Bhaban in order to uncover their mental maps and to reveal their untold secrets and sufferings. Zaynab, Din Tarini, Saudamini, Helen, Quaresa, Usha, Rafia, Sakina and others sit together to unfurl and speak their minds among themselves. Through their reminiscences and memories, Rokeya lays bare the angst of women under a patriarchal social order. Most of these women at Tarini Bhaban are considered ‘evil’ beyond its premise in one way or another. For example, Saudamini is a stepmother with no biological children of her own. Within the stepfamily, she is regarded as a dakini (witch) and rakshasi (a female demon). Other women of Tarini Bhaban received comparable tags from society and have similar stories to tell. Based on the representation of ‘evil’ women in Rokeya’s work, in this paper I will explore some of the contributing factors associated with the characterization of women as wicked in the context of twentieth-century Bengal.